Can you explain these two marked steps?

Please find below the solution to the asked query:

we consider previous step : tan θ Cos A + Sin ASin ACos Atan θ Cos B + Sin BSin B Cos B = 1 , So

tan θ Cos ASin ACos A + Sin ASin ACos Atan θ Cos BSin B Cos B + Sin BSin B Cos B = 1tan θ ×Cos A×Cos ASin A×Cos A + Sin A×Sin ASin A×Cos Atan θ ×Cos B×Cos BSin B×Cos B + Sin B×Sin BSin B×Cos B = 1tan θ ×Cos ASin A + Sin ACos Atan θ ×Cos BSin B + Sin BCos B = 1tan θ × Cos A Sin A +  Sin A Cos Atan θ × Cos B Sin B +  Sin B Cos B = 1
Hope this information will clear your doubts about topic.
 

  • 1
Thumps up

  • 0
What are you looking for?